2008
DOI: 10.1027/1614-0001.29.2.80
|View full text |Cite
|
Sign up to set email alerts
|

Anger Elicitation Using Affective Pictures:

Abstract: In emotion research, affective pictures are limited in their ability to elicit discrete emotions. The current study attempted to elicit anger using pictures and a person by image-content interactional strategy. In two studies, undergraduates who varied with respect to concern for animal welfare (person factor) were shown pictures that included several of actual or impending animal harm (image content). Results from Study 1 showed that (1) the link between animal concern and combined emotion outcomes was strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…For example, only one film reached the criterion to be included in the category "anger." This result is consistent with those of previous studies showing that emotional pictures are not an effective means to elicit anger in the laboratory (e.g., Mikels et al, 2005;Thibodeau, Jorgensen, & Jonovich, 2008) and indicates that film clips are also not effective as anger elicitors (see also Gross & Levenson, 1995).…”
Section: Discussionsupporting
confidence: 92%
“…For example, only one film reached the criterion to be included in the category "anger." This result is consistent with those of previous studies showing that emotional pictures are not an effective means to elicit anger in the laboratory (e.g., Mikels et al, 2005;Thibodeau, Jorgensen, & Jonovich, 2008) and indicates that film clips are also not effective as anger elicitors (see also Gross & Levenson, 1995).…”
Section: Discussionsupporting
confidence: 92%
“…As to the visual recognition of emotional information, developmental researchers have used emotional facial expressions as ecologically valid, salient stimuli even for very young children (McClure, 2000), although the ability of affective pictures to elicit discrete emotions has been questioned (Thibodeau, Jorgensen, & Jonovich, 2008). In a visual search task with memory updating demands (testing immediate recognition), Visu-Petra, Tincaş, Cheie, and Benga (2010) found that, compared to LA children, HA children were slower and less accurate in recognizing previously seen identities displaying happy expressions, but more accurate in responses to identities expressing anger.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are consistent with findings in the empathy literature that compassion is similarly strong for animals as for human babies in need of medical care (Angantyr et al, 2011) and that experimentally induced compassion for victims increases moral outrage against transgressors (Pfattheicher et al, 2019). Yet anger emerged as the primary response to images of animal abuse in a study of emotion-eliciting stimuli by Thibodeau et al (2008). Therefore, more research is needed to investigate the comparative importance of compassion and anger reactions to animal abuse cases.…”
Section: Discussionmentioning
confidence: 99%